Sertifikasi dan Implikasinya dalam Meningkatkan Kompetensi Profesional Guru - Zulkifli Musthan; Sarjaniah Zur (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This descriptive qualitative research aims to determine the professional competence of Islamic religious education teachers and the implications of certification in improving their professionalism. Data was collected through observation and interviews using snowball and purposive sampling. The results of qualitative data analysis indicate that Islamic religious education teachers have implemented materials, structures, concepts and some relevant knowledge related to Islamic education in schools. They also possess the competence in designing and applying knowledge in the context of learning and mastering basic competencies based on their knowledge for curriculum development. Teachers have social, professional, pedagogical and digital literacy competencies for everyday learning. The implications of this certification program can be useful in the world of education.Keywords: Certifications; Islamic educational teachers; teachers competence and professionalism; vocational school